Association between leisure sedentary behaviour and uterine fibroids in non-menopausal women: a population-based study - Qian Wang; Yi Li; Jianzhong Yin; Qiong Meng; Yunrui Sun; Xiaoyu Han; Zhongxin Hou; Haoyuan Deng; Nan Cheng; Nishang Zhang; Jianghui Zhang (BMJ Open, 2023)
Objective Sedentary behaviour is associated with a variety of adverse health outcomes, including obesity, oestrogen metabolism and chronic inflammation, all of which are related to the pathogenesis of uterine fibroids (UFs). This study aimed to explore the relationship between leisure sedentary time (LST) and UFs.Design Cross-sectional.Setting We conducted a cross-sectional analysis of data from patients from the Yunnan region in the China Multi-Ethnic Cohort Study.Participants A total of 6623 non-menopausal women aged 30–55 years old were recruited. Menstrual status was self-reported. Participants who lacked a unique national identity card, suffered from serious mental illness, did not have a clear diagnosis of UFs, or provided incomplete information were excluded.Primary and secondary outcome UFs were diagnosed by abdominal B-ultrasound. Leisure sedentary behaviour was assessed by using a face-to-face questionnaire interview. Logistic regression and restricted cubic spline were employed to explore the relationship between LST and UFs.Results A total of 562 participants had UFs, with a prevalence rate of 8.5% (7.8%, 9.2%). Multivariate adjusted logistic regression analysis showed that the risk of UFs in women with LST≥6 hour/day was 2.008 times that in women with LST<2 hour/day (95% CI 1.230 to 3.279). The restricted cubic spline results showed that there was a linear dose‒response relationship between LST and UFs (p for non-linearity>0.05). According to the results of the stratified analysis for menstrual status and body mass index (BMI), there was a correlation between LST and the prevalence of UFs only in women with a BMI<24 kg/m2 or perimenopause.Conclusion LST was independently associated with the prevalence of UFs, and a linear dose‒response relationship was observed. Our study provides evidence on the factors influencing UFs, and further research is needed to propose feasible measures for UFs prevention.